2018
DOI: 10.21037/cdt.2017.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional speckle-tracking echocardiography: benefits and limitations of integrating myocardial mechanics with three-dimensional imaging

Abstract: Three-dimensional (3D) speckle-tracking echocardiography (3DSTE) is an advanced imaging technique designed for left ventricular (LV) myocardial deformation analysis based on 3D data sets. 3DSTE has the potential to overcome some of the intrinsic limitations of two-dimensional STE (2DSTE) in the assessment of complex LV myocardial mechanics, offering additional deformation parameters (such as area strain) and a comprehensive quantitation of LV geometry and function from a single 3D acquisition. Albeit being a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
200
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(243 citation statements)
references
References 87 publications
5
200
0
9
Order By: Relevance
“…In the present study, it was found that the feasibility of 3DSTE grew significantly as the operators gained experience. Our feasibility results are comparable to other groups …”
Section: Discussionsupporting
confidence: 87%
“…In the present study, it was found that the feasibility of 3DSTE grew significantly as the operators gained experience. Our feasibility results are comparable to other groups …”
Section: Discussionsupporting
confidence: 87%
“…Moreover, LV systolic dysfunction in the form decreased LV EF obtained by 4D‐LVQ tool and decreased all cardiac strains were detected in the absence of cardiac symptoms. Feasibility and accuracy of 3D‐STE depend mainly on the quality of the images obtained that can be increased by choosing the sufficient frame rate, optimizing the gain, reducing the depth to include the entire LV cavity in the image sector, the acquisition of image during breath hold to avoid breathing artifacts and the choice of a well‐trained operator …”
Section: Discussionmentioning
confidence: 99%
“…To avoid these limitations, a 3D‐STE was recently developed to provide rapid image acquisition with a shorter scan time independent of operator skills due to simultaneous data analysis of different strains, LV volume and LV EF . Major disadvantages of 3D‐STE are that it mainly depends on the quality of the images, the patients’ cooperation for breath holding, and the regularity of the heart rate …”
Section: Discussionmentioning
confidence: 99%
“…Two‐dimensional strain imaging cannot completely track the spatial position of speckles, and offers poor accuracy, whereas 3D‐STE traces their motion in three‐dimensional space without angle‐dependence. It can evaluate segmental myocardial strain from multiple directions and quantitatively evaluate regional or global ventricular function . It is also more accurate than 2D‐STE in evaluating myocardial function.…”
Section: D‐ste In Assessing Myocardial Motionmentioning
confidence: 99%
“…Two‐dimensional speckle tracking echocardiography (2D‐STE) has been proved to be a good method for evaluating myocardial deformation and cardiac function in patients with renal insufficiency . Three‐dimensional speckle tracking echocardiography (3D‐STE) appears superior to 2D‐STE in analyzing the whole myocardial deformation during the same cardiac cycle, and has been recommended by several authors . It is especially suitable in patients with CRS in whom coronary angiography is contraindicated.…”
Section: Introductionmentioning
confidence: 99%